2010
DOI: 10.1039/b9nj00536f
|View full text |Cite
|
Sign up to set email alerts
|

Diels–Alder reaction of vinylene carbonate and 2,5-dimethylfuran: kinetic vs. thermodynamic control

Abstract: The Diels-Alder reaction between 2,5-dimethylfuran and vinylene carbonate was studied, both from an experimental and a theoretical point of view. The system was shown to slowly reach a thermodynamic equilibrium, characterized by the almost exclusive formation of the exo isomer. We rationalized these results by a comparison with classical systems involving maleic anhydride, and highlighted the different reactivity of vinylene carbonate as a dienophile. Finally, a preparative scale synthesis of pure exo isomer 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…A quick optimization of the asymmetric dihydroxylation step (see ESI † ) showed that cis -osmilation using osmium tetroxide in presence of excess of N -methylmorpholine N -oxide provided the desired hexose-like structure. 13 Thus, compound 40 , containing six adjacent stereocenters, was obtained in 68% yield and with an exclusive 4,5- anti stereochemistry. The determination of the stereochemistry of the latter compound was based on the optimization reactions where we obtained the same single isomer using both chiral AD-mix-α or β with comparable selectivity but with a slower reaction rate (50% conversion after 4 days), which can be explained by the preferred attack of osmium from the opposite side of the free hydroxy group present in 39 .…”
Section: Resultsmentioning
confidence: 92%
“…A quick optimization of the asymmetric dihydroxylation step (see ESI † ) showed that cis -osmilation using osmium tetroxide in presence of excess of N -methylmorpholine N -oxide provided the desired hexose-like structure. 13 Thus, compound 40 , containing six adjacent stereocenters, was obtained in 68% yield and with an exclusive 4,5- anti stereochemistry. The determination of the stereochemistry of the latter compound was based on the optimization reactions where we obtained the same single isomer using both chiral AD-mix-α or β with comparable selectivity but with a slower reaction rate (50% conversion after 4 days), which can be explained by the preferred attack of osmium from the opposite side of the free hydroxy group present in 39 .…”
Section: Resultsmentioning
confidence: 92%
“…The first example of kinetic/thermodynamic control in the course of the Diels-Alder reaction was reported in 1948 (Woodward & Baer, 1948). Since then, the reversibility of the [4 + 2] cycloaddition was observed many times for examples of a broad range of dienes and dienophiles, including alkynes and furans (Boutelle & Northrop, 2011;Taffin et al, 2010;White et al, 2000;Marchand et al, 1998;Manoharan & Venuvanalingam, 1997;Bott et al, 1996;Bartlett & Wu, 1985). From this diversity of diene/dienophile combinations, tandem and domino reactions of the [4 + 2] cycloaddition based on acetylenic dienophiles are more interesting for the total synthesis of natural or bioactive products (Sears & Boger, 2016;Parvatkar et al, 2014;Winkler, 1996).…”
Section: Chemical Contextmentioning
confidence: 99%
“…dropwise; a white precipitate appeared. The resulting mixture was stirred at room temperature for 3 h. After dilution with AcOEt (50 mL), the mixture was quenched with a saturated aqueous NH 4 Cl solution (40 mL), and the layers were separated. The organic layer was washed successively with water (40 mL), 1 n HCl (2 ϫ 40 mL), water (40 mL), and brine (40 mL).…”
Section: 4-dimethyl-7-oxabicyclo[221]hept-5-ene-23-diyl Dibenzoamentioning
confidence: 99%
“…[3] During our studies on the Diels-Alder reaction between 1 and 2, we evidenced that prolonged heating leads to clean conversion of the endo/exo mixture into exo adduct 3 only, enabling large-scale production of the latter on a preparative scale after direct crystallization. [4] Therefore, we decided to exploit this result to design another route to 1Ј,4Ј-dimethyl nucleoside analogues, which is both shorter and suitable for purine synthesis (Scheme 1). It is the purpose of this communication to report our first results regarding this approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation